Bladder Health in U.S. Shift Workers: A Cross-Sectional Study (NHANES) - Diao, Jianjun; Xie, Li; Wu, Bo; Chen, Lin; Jing, Hao (Urology Journal, 2025)
Purpose: Working during non-traditional hours is becoming more prevalent in modern societies and presents a significant hurdle to an individual's circadian rhythm. We examined the bladder health of shift workers in the United States by analyzing information obtained from the National Health and Nutrition Examination Survey. Materials and methods: National Health and Nutrition Examination Survey (NHANES) datasets from 2005 to 2010 were utilized. Regression analyses were used to assess the association between shift work and bladder health (stress incontinence, urge incontinence, and nocturia) by adjusting for age, race, education, smoking, and other factors. Results: The percentage of non-Hispanic Black individuals was notably higher among shift workers (25.8% vs. 17.8%). Among shift workers, there was a lower percentage of individuals with a college degree or higher compared to day workers. Shift work was found to be associated with nocturia in men in the unadjusted model (OR=1.2, 95%CI=1.0-1.5, p = 0.038). However, the adjusted results indicate that the connection is not statistically significant (Adjusted Model II: OR=1.2, 95%CI=1.0-1.5, p = 0.105). Similarly, no statistically significant association was observed between shift work and nocturia in women. There was also no significant relationship between shift work and Stress Urinary Incontinence (SUI) in men or women. The results from the fully adjusted model (Adjusted Model II) indicate a significant association between shift work and the prevalence of Urgency Urinary Incontinence (UUI) in women (OR=1.2, 95%CI=1.0-1.5, p = 0.041). Conclusion: Results of this cross-sectional study indicated that shift work was associated with a higher risk of UUI in women. Further research is needed to explore this relationship.